Peringatan Otomatis Pada Internet of Things Sistem Deteksi Smart Motion - Anwar, Nizirwan; Tjahjono, Budi; Tarigan, Masmur; Adhy Rosian, Dewanto; Widiyasono, Nur; Hermawan, Rudi (Generation Journal, 2021)
The main problem in this research is the increase in cases of theft and robbery. This incident was caused by the busyness of everyone in their daily lives, so they forgot about the safety of their house. An Internet of Things (IoT) based home security system that utilizes a PIR sensor as a human motion detector and then sends a notification in the form of a notification via SMS or e-mail is one solution to overcome the problems that have been previously proposed in previous research. However, to further clarify the warning sent from the system, a home security system is needed that can attach an image to the notification. In this study, an IoT-based home security system was developed. The IoT security system being developed can automatically send a warning message by attaching an image when the PIR sensor detects human presence. The IoT system requires a Raspberry Pi as a microcontroller that is connected to the internet, a PIR sensor to detect human movement and a Pi Camera to win an image when there is an encounter with a human within the range of the PIR sensor. Experiments in this study show that the IoT system can automatically send warning messages via the Telegram application by attaching an image when the PIR sensor detects human presence in various light conditions with a distance of 0-5 meters and the speed of sending email alerts is influenced by the condition of the internet network connection and file size. images sent.